2002
DOI: 10.3184/030823402103172095
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Site and Proton Transfer Equilibrium in the 4-Aminoantipyrine-Pentachlorophenol Hydrogen–Bonded Adduct

Abstract: The hydrogen-bonding interaction site between 4-aminoantipyrine (4AAP) and pentachlorophenol (PCP) was investigated in the crystalline form using FT-IR and in solution using FT-IR, UV-Vis and 1H,13C NMR spectroscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The result obtained in the PCP complexes is consistent with the inversion point of 35 Cl NQR frequencies [ 12 , 28 ]. In PCP–4MP, a proton transfer and isotope polymorphism have been reported [ 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Since the large 1 H-NMR CS value of 18.6 ppm was recorded in TCP–IMID as compared with 17.8 ppm of PCP–4MP, it can be expected that the similar properties are obtained in TCP–IMID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result obtained in the PCP complexes is consistent with the inversion point of 35 Cl NQR frequencies [ 12 , 28 ]. In PCP–4MP, a proton transfer and isotope polymorphism have been reported [ 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Since the large 1 H-NMR CS value of 18.6 ppm was recorded in TCP–IMID as compared with 17.8 ppm of PCP–4MP, it can be expected that the similar properties are obtained in TCP–IMID.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of pentachlorophenol (abbreviated to PCP) complexes, it has been reported that PCP forms salts with nitrogen-bases (N-Base) covering a broad p K a range (0.65–11.20). These crystals have been employed to detect proton-transfer equilibrium between O–H···N (covalent form) and O − ···H–N + (ionic form) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. 35 Cl NQR frequency measurements have reported that the NQR frequencies give constant values of ca .…”
Section: Introductionmentioning
confidence: 99%